Ayatollah Javadi Amoli's Perspective on Redemption: Inclusive End or Dominant End? - Tahereh Salehi; Yahya Sabbaghchi (حکمت اسرا, 2024)
Among the important and controversial issues about Redemption are the two interpretations of Inclusive and dominant End of Redemption. These two interpretations are analyzed based on the degree of effectiveness of the factors involved in Redemption. According to the Inclusive End interpretation, Redemption is a concept that has several components, each of which has independent value; and according to the dominant End interpretation, Redemption has only one constituent component, and other components are the introduction or means of achieving that true Redemption. This article seeks to explore the views of Ayatollah Javadi Amoli on the nature of Redemption and the explanation of transcendental Redemption, and to answer the question of whether his view of Redemption is an interpretation of the dominant End or a Inclusive End. The result of this research is that transcendental Redemption in his works is as the existential perfection of the soul, and scientific, practical, rational and religious virtues are an introduction to achieving this Redemption. Therefore, his view is more in line with the dominant interpretation of Redemption. The descriptive-analytical method has been used in presenting and presenting the findings of this research.